2012
DOI: 10.6002/ect.2012.0017
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Endovascular Repair in a Patient With Abdominal Aortic Aneurysm With Pelvic Transplant Kidneys: Case Report

Abstract: Abdominal aortic aneurysms after a kidney transplant are becoming treated more frequently owing to the extension of renal transplant in severely arteriosclerotic older patients. Renal transplant recipients with autosomal dominant polycystic kidney disease are prone to develop abdominal aortic aneurysms. We present the case of a ruptured abdominal aortic aneurysm that occurred in a renal transplant patient with autosomal dominant polycystic kidney disease. The patient was treated with emergency endovascular rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Different techniques have been introduced to reduce the risk of ischemia during open surgery repairs, such as axillofemoral bypass, aortoiliac bypass, femoral artery to femoral vein bypass with pump oxygenators, local allograft cooling, mannitol and fluid loading [ 7 , 9 ]. However, none has proved to have any more advantage than a ‘clamp-and-go’ strategy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been introduced to reduce the risk of ischemia during open surgery repairs, such as axillofemoral bypass, aortoiliac bypass, femoral artery to femoral vein bypass with pump oxygenators, local allograft cooling, mannitol and fluid loading [ 7 , 9 ]. However, none has proved to have any more advantage than a ‘clamp-and-go’ strategy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular aortic aneurysm repair (EVAR), is widely proven to have better early results when compared to open surgery (OS) [ 10 ], although there is evidence that females who received either OS or EVAR, remain at higher risk of postoperative mortality than males [ 11 ]. Previous studies showed the disparities of risks and outcomes of AAA between the two sexes, on the basis of a unique treatment indistinctly used either electively or in emergency [ 12 , 13 , 14 ], with far worse outcomes in females. Furthermore, there are inherent morphological dissimilarities between male and female patients, as the disease is intrinsically different among the two sexes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An association with other systemic manifestations is also frequent: polycystic liver disease, mitral valve prolapse or ventricular hypertrophy [8], intracranial aneurysm, abdominal aortic aneurysm [7], diverticular disease [5], and bronchiectasis [8]. For abdominal aortic aneurysm in particular, they tend to expand more rapidly in transplanted patients, and in the case of massively enlarged polycystic kidneys, the surgical access for a ruptured abdominal aortic aneurysm could be very challenging [9]; therefore variation in clinical symptoms has to be carefully assessed.…”
Section: Introductionmentioning
confidence: 99%